Religious Attention During The Samaritans - Mo'ydinov Muhammadali (Peerian Journals Publishing, 2023)
In this article, we aim to provide information about the attitude towards religion in the Samanid state, which ruled Movarounnahr as a strong empire for nearly a century and a half.
Keywords: Samanids; Bukhara; Samarkand; Nuh